2013
DOI: 10.1039/c2nr32949b
|View full text |Cite
|
Sign up to set email alerts
|

Substrate coupling suppresses size dependence of thermal conductivity in supported graphene

Abstract: Thermal conductivity κ of both suspended and supported graphene has been studied by using molecular dynamics simulations. Obvious length dependence is observed in κ of suspended single-layer graphene (SLG), while κ of supported SLG is insensitive to the length. The simulation result of room temperature κ of supported SLG is in good agreement with experimental value. In contrast to the decrease in κ induced by inter-layer interaction in suspended few-layer graphene (FLG), κ of supported FLG is found to increase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
143
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 195 publications
(162 citation statements)
references
References 33 publications
16
143
2
1
Order By: Relevance
“…In our simulations, the width of simulation cell is set as 5. is consistent with previous studies 35,36 .…”
Section: Resultssupporting
confidence: 94%
“…In our simulations, the width of simulation cell is set as 5. is consistent with previous studies 35,36 .…”
Section: Resultssupporting
confidence: 94%
“…Page 7 Along the heat transfer direction (longitudinal), the thermal conductivity depends on the length of material in nanoscale. Previous works 14,21,46 on graphene found that the thermal conductivity increases as the length of graphene increases and the thermal conductivity does not converge even at several micrometers. We study the κ GPnC dependence on the length of GPnCs at room temperature, which is shown in Fig.…”
Section: Simulation Resultsmentioning
confidence: 93%
“…On the amorphous silicon dioxide substrate, both the theoretical [124] and experimental [122] studies show that thermal conductivity of supported multi-layer graphene saturates to that of bulk graphite at the thickness of about 40 layers. Similar thickness-dependence behavior also was observed by several independent groups on black phosphorous [73,111,112], and MoS 2 [108].…”
Section: Thickness/number Of Layers Dependence Of Phonon Thermal Tranmentioning
confidence: 99%